Business Environment and the Incorporation Decision - Demirguc-Kunt, Asli; Love, Inessa; Maksimovic, Vojislav (World Bank, Washington, D.C., 2013)
Using firm-level data from 52 countries, the authors investigate how a country's institutions and business environment affect firms' organizational choices and the effects of organizational form on access to finance and growth. They find that businesses are more likely to choose the corporate form in countries with developed financial sectors and efficient legal systems, strong shareholder and creditor rights, low regulatory burdens and corporate taxes, and efficient bankruptcy processes. Corporations report fewer financing, legal, and regulatory obstacles than unincorporated firms, and this advantage is greater in countries with more developed institutions and favorable business environments. The authors find some evidence of higher growth of incorporated businesses in countries with good financial and legal institutions.